2020
DOI: 10.3389/fphar.2020.00597
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of HES on Vascular Permeability and Its Relationship With Endothelial Glycocalyx and Intercellular Junction After Hemorrhagic Shock

Abstract: Background: Vascular leakage is a common complication of hemorrhagic shock. Endothelial glycocalyx plays a crucial role in the protection of vascular endothelial barrier function. Hydroxyethyl starch (HES) is a commonly used resuscitation fluid for hemorrhagic shock. However, whether the protective effect of HES on vascular permeability after hemorrhagic shock is associated with the endothelial glycocalyx is unclear.Methods: Using hemorrhagic shock rat model and hypoxia treated vascular endothelial cells (VECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…Vascular endothelial cells were obtained from pulmonary veins of SD rats, as described previously ( Zhao et al, 2020 ). Rats were anesthetized and sterilized with iodine, and then rats received thoracotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Vascular endothelial cells were obtained from pulmonary veins of SD rats, as described previously ( Zhao et al, 2020 ). Rats were anesthetized and sterilized with iodine, and then rats received thoracotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from Zhao et al show that hydroxyethyl starch (130/0.4) has a protective effect on the vascular barrier function after hemorrhagic shock, and its mechanism is mainly related to the downregulation of heparinase, hyaluronidase, and neuraminic acid by hydroxyethyl starch. The expression of enzymes is related to the protective effect of endothelial glycocalyx and intercellular junction protein (27). In one study, Jacob et al injected physiological concentrations of type A, type B, and type C natriuretic peptides into the coronary arteries, and found that there were eluted glycocalyx components (proteoglycan-1 and heparan sulfate) in the coronary veins, the functional vascular barrier ability had been reduced, and that the formation of leakage and the exudation of colloidal hydroxyethyl starch had increased significantly.…”
Section: Endothelial Surface Layer and Endothelial Glycocalyxmentioning
confidence: 99%
“…Degree of volume expansion and longevity of HES, or any colloid, in plasma is difficult to predict. It will depend not only on the degree of vascular injury, but also on the MW and dispersity, amylase concentration, elimination rate into the urine, as well as its electrical charge, shape, and effect on the endothelial glycocalyx (31)(32)(33)(34)(35)(36)(37). Studies focusing on the immunologic, coagulation, and renal effects of HES products are not all in agreement, and species differences may exist (editor-See Article 7 Colloids, Yes or No?…”
Section: Synthetic Colloidsmentioning
confidence: 99%